Effect of Season on Hampshire Crossbreed Boar Semen Quality and Antioxidant Status under Hot Humid Sub Tropical Climate - Singh, Mahak; Celina, Apani; Nguillie, Ebibeni; Katiyar, Rahul; Deori, Sourabh; Chamuah, Jayanta; Kalita, Homeswar; Kumar Mishra, Vinay (The Indian Journal of Animal Reproduction, 2025)
The present investigation aimed to study the season’s effecton semen quality,and antioxidant status of Hampshire cross bred boar in sub-tropical climatic condition. For the present experiment, same six Hampshire crossbreed boars were used in summer and winter season. Sperm quality parameters (SQPs) were assessed microscopically. Computer-assisted semen analysis (CASA) was used to assess sperm kinematics. Antioxidants biomarkers (glutathione peroxidase; GPx, catalase; CAT, total antioxidant capacity; TAC) and lipid peroxidation (malondialdehyde; MDA) were measured in boar’s seminal plasma. Summer season had significant (p < 0.01) negative effect on reaction time and false mounts. Semen volume and sperm concentration was recorded to be significantly (p < 0.01) higher in winter season. Sperm total motil ity, progressive motility, viability, acrosomal integrity and HOST reactive sperm were recorded to be significantly (p < 0.01) higher in winter season. Season had a significant (p < 0.05) effect on the sperm velocity attributes.Seminal plasma antioxidant biomarkers (TAC, MDA, CAT and GPx) were significantly (p < 0.01) affected by summer season. In con clusion, the Hampshire crossbreed boar’s semen quality and antioxidant biomarkers were negatively affected in summer season. There is need of intervention in terms of genetic, nutrition and management to optimize the boar fertility during summer months in sub-tropics.